First verified records in Ukraine of Diaporthe caulivora (Diaporthales, Ascomycota), a causal agent of northern stem canker of soybean - Krasnopirka V.A.; Zabolotnia A.S.; Akulov O.Yu. (Ukrainian Botanical Journal)
Soybean is one of the most important crops in Ukraine, and the area planted with this crop has increased since the beginning of the full-scale war. Originated in Southeast Asia, soybean is cultivated in Ukraine for a relatively short time. Most pathogens affecting soybeans here are alien species, with some of them recently introduced to the country. Based on molecular studies of two pure cultures isolated from the infected soybean seeds grown in the western regions of Ukraine, we identified Diaporthe caulivora causing northern stem canker in soybeans. This is the first verified record of the species in Ukraine. This article provides morphological and cultural characteristics of the fungus, along with the diagnostic methods for detection of the disease in seed samples. Special attention is paid to a brief history of studies of the genus Diaporthe since its description in the 19th century until present. The species composition of the Diaporthe pathogens of soybeans is analyzed, with information on the reports of certain species in Europe which may occur in Ukraine.